Tuberculous sacroiliitis: a case report - Khakandaki, Sarvesh; Kamashetty, Nikita; Mudgall, Gurusangappa; Paritekar, Pranav; Upadhyay, Keyur (International Journal of Research in Orthopaedics, 2021)
In 1-5% of cases of the infections of the musculoskeletal system are tuberculous. The sacroiliac joint (SI) shows involvement in 3-9.7%. Here, we describe the unique case of a 19-year-old female who presented with pain in the left buttock and low backache. Three months prior, the patient was diagnosed with pulmonary tuberculosis. The patient was started on anti-tuberculosis drugs (ATT) for three months. The pain increased on weight-bearing and on squatting, and it decreased with rest. X-ray and MRI were suggestive of Sacroiliitis secondary to tuberculosis. Now, after conservative management, the patient is symptom-free with no functional limitation. This case report focuses on the importance of continued awareness for early detection and treatment of a tuberculous sacroiliac joint infection.